Composite diaphragm and preparation method and application thereof
Patent Information
- Application Number
- CN202611243729.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-23
AI Technical Summary
所述复合隔膜具有较大的有效工作面积(离子传输面积),气泡在其表面停留时间短,解决了现有技术中碱性电解水制氢槽在高电流密度下因气泡屏蔽效应导致的电压升高问题
本发明提供的复合隔膜,所述复合隔膜采用特定的结构设计,即设计为具有不同粗糙度的两个表面,且第一表面分布有点状凸起结构,应用时,第一表面靠近阳极,第二表面靠近阴极,提高了复合隔膜有效工作面积,气泡在其表面停留时间短,解决了现有技术中碱性电解水制氢槽在高电流密度下因气泡屏蔽效应导致的电压升高问题。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of alkaline water electrolysis for hydrogen production technology, specifically relating to a composite membrane, its preparation method, and its application. Background Technology
[0002] Alkaline water electrolysis is one of the key technologies for green hydrogen production. Electrolysis of water in KOH solution can stably produce high-purity hydrogen and oxygen. During this process, hydrogen and oxygen bubbles are continuously generated on the electrode surface. Under low current density conditions, the bubbles can quickly detach and escape; however, under high current density, the bubble generation rate increases sharply, and a large number of bubbles adhere to and cover the electrode and membrane surfaces.
[0003] However, the shielding effect of bubbles (i.e., the aforementioned large number of bubbles adhering to and covering the surface of the electrodes and the diaphragm) not only blocks the ion transport channels and significantly reduces the effective working area of the diaphragm, but also, since the bubbles themselves are insulators, they form a "cushion" layer in the electrolyte, increasing the path and resistance of ion transport between the electrodes, resulting in an increase in the voltage of the alkaline water electrolysis hydrogen production cell (referred to as the electrolyzer).
[0004] Therefore, developing a diaphragm that can solve the problem of voltage rise in electrolyzers under high current density is an urgent problem to be solved in this field. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a composite membrane, its preparation method, and its applications. The composite membrane has a large effective working area (ion transport area), and bubbles have a short residence time on its surface, thus solving the problem of voltage rise caused by bubble shielding effect in existing alkaline water electrolysis hydrogen production cells under high current density.
[0006] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a composite diaphragm having a first surface and a second surface disposed opposite to each other; the roughness Ra of the first surface is 0.8~6μm; the roughness Ra of the second surface is ≤0.7μm; and the first surface is distributed with dot-shaped protrusions.
[0007] In this invention, the composite diaphragm adopts a specific structural design, namely, it uses two surfaces with different roughnesses. The first surface is non-planar with dotted protrusions, while the second surface is designed with a relatively simple structure, or even remains flat. In application, the first surface is close to the anode, which helps the bubbles to detach quickly, while the second surface is close to the cathode, which ensures the wettability of the electrolyte, reduces the interface resistance, avoids the problem of increased electrolytic cell voltage caused by the bubble shielding effect under high current density, and improves the effective working area of the composite diaphragm.
[0008] In a second aspect, the present invention provides a method for preparing the composite separator according to the first aspect, the method comprising the following steps: (1) Provide a substrate; and lay the substrate flat and fix it to one side of the first polydimethylsiloxane template; (2) Prepare a first coating slurry and coat the first coating slurry onto a surface of the substrate away from the first polydimethylsiloxane template. Then, the substrate is subjected to pre-evaporation, phase inversion and peeling off of the first polydimethylsiloxane template in sequence to obtain a substrate with the first coating layer on the surface. (3) Prepare a second coating slurry and coat the second coating slurry onto the surface of the substrate away from the first coating layer, and then perform pre-evaporation and phase inversion in sequence to obtain the composite membrane.
[0009] Thirdly, the present invention provides an alkaline water electrolysis device, the alkaline water electrolysis device comprising at least one of the following: (1) The composite diaphragm described in the first aspect; (2) The composite diaphragm prepared by the preparation method described in the second aspect.
[0010] Compared with the prior art, the beneficial effects of the present invention are as follows: The composite diaphragm provided by this invention adopts a specific structural design, namely, it is designed with two surfaces with different roughnesses, and the first surface is distributed with dot-shaped protrusions. In application, the first surface is close to the anode and the second surface is close to the cathode, which increases the effective working area of the composite diaphragm and reduces the residence time of bubbles on its surface. This solves the problem of voltage rise caused by bubble shielding effect in alkaline water electrolysis hydrogen production cells under high current density in the prior art. Detailed Implementation
[0011] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0012] The present invention provides a composite diaphragm having a first surface and a second surface disposed opposite to each other; the roughness Ra of the first surface is 0.8~6μm; the roughness Ra of the second surface is ≤0.7μm; and the first surface is distributed with dot-shaped protrusions.
[0013] Traditional membranes have two smooth, flat surfaces, allowing air bubbles to easily and randomly accumulate anywhere. The composite membrane provided by this invention employs a specific structural design: the first surface has a higher roughness than the second surface, and the first surface is designed with dotted protrusions. This actively guides air bubbles, providing them with high points. Driven by hydrophobic forces, the bubbles tend to move directionally towards these high points (such as crests or the tops of protrusions). During this movement, small bubbles merge into larger bubbles, which, when buoyancy is sufficient, quickly detach from the composite membrane surface, avoiding the bubble shielding effect. This also increases the effective working area of the composite membrane. Even when covered by air bubbles, only the crests are covered, while the troughs still maintain ion transport, thus reducing the voltage of the electrolyzer at high current densities. The second surface has a relatively low roughness and is designed with a simple, even flat, structure. This maximizes electrolyte wetting without affecting the adhesion between the composite membrane and the electrode, increasing the OH- concentration. - The present invention improves the conductivity and reduces the interface resistance. In summary, the present invention adopts a composite membrane with a first surface close to the anode and a second surface close to the cathode, which increases the effective working area of the composite membrane and reduces the residence time of bubbles on its surface. This solves the problem of voltage rise caused by bubble shielding effect in alkaline water electrolysis hydrogen production cells under high current density in the prior art.
[0014] In this invention, the first surface and the second surface of the composite membrane, which are arranged opposite to each other, refer to the two surfaces of the composite membrane that are opposite to each other in the thickness direction.
[0015] In this invention, the roughness Ra of the first surface is 0.8~6μm, for example, it can be a range of 0.8μm, 1μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm, 2μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm, 3μm, 3.2μm, 3.4μm, 3.6μm, 3.8μm, 4μm, 4.2μm, 4.4μm, 4.6μm, 4.8μm, 5μm, 5.2μm, 5.4μm, 5.6μm, 5.8μm or any combination thereof.
[0016] In this invention, the roughness Ra of the second surface is ≤0.7μm, and for example, it can be a range of 0.01μm, 0.02μm, 0.04μm, 0.06μm, 0.08μm, 0.1μm, 0.12μm, 0.14μm, 0.16μm, 0.18μm, 0.2μm, 0.22μm, 0.24μm, 0.26μm, 0.28μm, 0.3μm, 0.32μm, 0.34μm, 0.36μm, 0.38μm, 0.4μm, 0.42μm, 0.45μm, 0.48μm, 0.5μm, 0.52μm, 0.55μm, 0.58μm, 0.62μm, 0.65μm, 0.7μm, or any combination thereof.
[0017] In this invention, the test method for roughness Ra is as follows: the test is carried out in accordance with the standard GB / T1031-2009.
[0018] In some specific embodiments of the present invention, the difference in roughness Ra between the first surface and the second surface is 1.5~5μm, for example, it can be a range of 1.6μm, 1.8μm, 2μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm, 3μm, 3.2μm, 3.4μm, 3.6μm, 3.8μm, 4μm, 4.2μm, 4.4μm, 4.6μm, 4.8μm, 5μm or any two of them.
[0019] In this invention, the roughness of the first surface and the second surface, as well as the difference between their roughnesses, are within the above-mentioned range, which helps to reduce the voltage of the electrolytic cell while maintaining high adhesion to the electrolytic cell and ensuring good airtightness.
[0020] In some specific embodiments of the present invention, the dot-shaped protrusion structure is selected from a dot-shaped protrusion structure without sharp edges, preferably at least one of an arc protrusion structure, a mushroom-shaped protrusion structure, and a coral-shaped protrusion structure, and more preferably an arc protrusion structure.
[0021] In this invention, the cross-sectional shape of the dot-shaped protrusions on the first surface can be any pointless protrusion. Using pointless protrusions facilitates the rapid detachment of bubbles from the composite membrane surface, reducing the impact of bubble shielding effect on ion conduction efficiency and further affecting the electrolytic cell voltage.
[0022] In some specific embodiments of the present invention, the first surface satisfies at least one of the following: (a) The number of dot-like protrusions on the first surface is 50 to 250 per mm. 2 For example, it can be 50 pieces / mm 2 70 pieces / mm 2 90 pieces / mm 2110 pieces / mm 2 130 pieces / mm 2 150 pieces / mm 2 170 pieces / mm 2 190 pieces / mm 2 210 pieces / mm 2 230 pieces / mm 2 250 pieces / mm 2 Or a range consisting of any two of them.
[0023] In this invention, the number of dot-shaped protrusions on the first surface is within the above-mentioned range, which facilitates the rapid detachment of bubbles from the composite membrane surface, reduces the impact of bubble shielding effect on ion conduction efficiency, and further reduces the electrolytic cell voltage.
[0024] (b) The distance between any two adjacent point-like protrusions on the first surface is 60~100μm, for example, it can be a range of 60μm, 62μm, 64μm, 66μm, 68μm, 70μm, 72μm, 74μm, 76μm, 78μm, 80μm, 82μm, 84μm, 86μm, 88μm, 90μm, 92μm, 94μm, 96μm, 98μm or any two of them.
[0025] It is understood that in this invention, the dot-shaped protrusions are separated from each other, and there is no contact or overlap between any two protrusions.
[0026] In this invention, the spacing between any two adjacent dot-shaped protrusions on the first surface is within the above-mentioned range, which can better match the critical desorption size of oxygen bubbles on the anode side under alkaline water electrolysis hydrogen production conditions. By utilizing the steric hindrance effect, the stable attachment state of the bubbles is disrupted, effectively reducing the attachment and retention of oxygen bubbles on the membrane surface, and significantly reducing the voltage of the electrolyzer.
[0027] (c) The diameter of the dot-shaped protrusions on the first surface is 20~50μm, for example, it can be 20μm, 22μm, 24μm, 26μm, 28μm, 30μm, 32μm, 34μm, 36μm, 38μm, 40μm, 42μm, 44μm, 46μm, 48μm, 50μm or any combination thereof.
[0028] (d) The height of the dot-shaped protrusions on the first surface is 10~50μm, for example, it can be a range of 12μm, 14μm, 16μm, 18μm, 20μm, 22μm, 24μm, 26μm, 28μm, 30μm, 32μm, 34μm, 36μm, 38μm, 40μm, 42μm, 44μm, 46μm, 48μm or any two of them.
[0029] In this invention, the diameter and height of the dot-shaped protrusions on the first surface are within the above-mentioned range, which is conducive to the rapid detachment of bubbles, while ensuring that the composite diaphragm is tightly attached to the anode side without increasing the contact resistance.
[0030] (e) The relative standard deviation (RSD) of the height of the dotted protrusions on the first surface is 0 to 4%, for example, it can be a range of 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8% or any combination thereof.
[0031] In this invention, the relative standard deviation of the height of the dot-like protrusions on the first surface is within the aforementioned range, which can effectively reduce the fluctuation range of the interface impedance of the first surface and reduce the electrolytic cell voltage. The testing method is as follows: the randomly distributed protrusions on the first surface are scanned under a 50× / 20 objective lens using a confocal microscope (purchased from Keyence) to obtain their three-dimensional morphology image. With the substrate plane as a reference, the average height h and standard deviation σ are measured. The RSD calculation formula is RSD=σ / h×100%.
[0032] In some specific embodiments of the present invention, the second surface is provided with dotted protrusions.
[0033] In this invention, the second surface is more preferably a surface with a dotted protrusion structure, which helps to increase the contact area between the second surface and the cathode-side electrolyte, thereby promoting OH... - The migration.
[0034] In this invention, the dot-shaped protrusion structure of the second surface is selected from a dot-shaped protrusion structure without sharp edges, preferably at least one of an arc protrusion structure, a mushroom-shaped protrusion structure, and a coral-shaped protrusion structure, and more preferably an arc protrusion structure.
[0035] Preferably, the second surface satisfies at least one of the following: (a) The number of dot-like protrusions on the second surface is 10 to 50 per mm. 2 For example, it can be 12 per mm. 2 14 pieces / mm 2 16 pieces / mm 2 18 pieces / mm 2 20 pieces / mm 2 22 pieces / mm 2 24 pieces / mm 2 26 pieces / mm 2 28 pieces / mm 2 30 pieces / mm 2 32 pieces / mm2 34 pieces / mm 2 36 pieces / mm 2 38 pieces / mm 2 40 pieces / mm 2 42 pieces / mm 2 44 pieces / mm 2 46 pieces / mm 2 48 pieces / mm 2 Or any two of them.
[0036] (b) The distance between any two adjacent point-like protrusions on the second surface is 100~300μm, for example, it can be a range of 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, 200μm, 210μm, 220μm, 230μm, 240μm, 250μm, 260μm, 270μm, 280μm, 290μm or any two of these values.
[0037] (c) The diameter of the dot-shaped protrusions on the second surface is 1 to 10 μm, for example, it can be a range of 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 7.0 μm, 7.5 μm, 8.0 μm, 8.5 μm, 9.0 μm, 9.5 μm or any combination thereof.
[0038] (d) The height of the dot-shaped protrusions on the second surface is 1~5μm, for example, it can be a range of 1.2μm, 1.4μm, 1.6μm, 1.8μm, 2.0μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm, 3.0μm, 3.2μm, 3.4μm, 3.6μm, 3.8μm, 4.0μm, 4.2μm, 4.4μm, 4.6μm, 4.8μm or any two of these values.
[0039] In this invention, the number, spacing, diameter, and height of the dot-like protrusions on the second surface are within the above-mentioned range, which ensures a larger electrolyte contact area and increases the OH- concentration. - It achieves high conduction efficiency without increasing additional interface impedance and without affecting the contact between the second surface and the electrode (cathode).
[0040] In some specific embodiments of the present invention, the composite membrane includes a first coating layer, a substrate, and a second coating layer disposed sequentially; the side of the first coating layer away from the substrate is a first surface; the side of the second coating layer away from the substrate is a second surface; the materials of the first coating layer and the second coating layer are the same or different, and each independently includes a first polymer and an inorganic material.
[0041] Preferably, the mass ratio of the first polymer to the inorganic material in the first coating layer is 1:(1.3~8), wherein the specific value of (1.3~8) can be, for example, a range of 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5 or any two of these; the mass ratio of the first polymer to the inorganic material in the second coating layer is 1:(1.2~5), wherein the specific value of (1.2~5) can be, for example, a range of 1.4, 1.6, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8 or any two of these.
[0042] Preferably, the first polymer includes at least one of polysulfone, polyethersulfone, polyphenylene sulfone, and polyetheretherketone.
[0043] Preferably, the inorganic material includes at least one of zirconium dioxide, titanium dioxide, barium sulfate, and barium zirconate.
[0044] In this invention, the size of the inorganic material is not specifically limited; for example, the particle size of the inorganic material can be 10~200nm, more preferably 30~100nm.
[0045] In this invention, the material of the substrate is not particularly limited; it is acceptable as long as it meets the conventional application in the art and the limitations of this application. For example, the material of the substrate includes at least one of polyphenylene sulfide (PPS), polypropylene (PP), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, and polyethylene naphthalate, more preferably polyphenylene sulfide.
[0046] In some specific embodiments of the present invention, the substrate is a mesh substrate, and the mesh count of the substrate is 40 to 60 mesh, for example, it can be 45 mesh, 50 mesh, 55 mesh or any combination thereof.
[0047] Preferably, the thickness of the substrate is 240~300μm, for example, it can be a range of 250μm, 260μm, 270μm, 280μm, 290μm or any combination thereof.
[0048] Preferably, the thickness of the composite membrane is 390~520μm, for example, it can be a range of 400μm, 420μm, 440μm, 460μm, 480μm, 500μm or any combination thereof. It is understood that the composite membrane includes a first surface and the height of the protrusions on the first surface.
[0049] In this invention, the porosity of the composite membrane is 50-75%, for example, it can be a range of 55%, 60%, 65%, 70%, or any two of these.
[0050] The present invention also provides a method for preparing the composite membrane according to the first aspect, the method comprising the following steps: (1) Provide a substrate; and lay the substrate flat and fix it to one side of the first polydimethylsiloxane template; (2) Prepare a first coating slurry and coat the first coating slurry onto a surface of the substrate away from the first polydimethylsiloxane template. Then, the substrate is subjected to pre-evaporation, phase inversion and peeling off of the first polydimethylsiloxane template in sequence to obtain a substrate with the first coating layer on the surface. (3) Prepare a second coating slurry and coat the second coating slurry onto the surface of the substrate away from the first coating layer, and then perform pre-evaporation and phase inversion in sequence to obtain the composite membrane.
[0051] In this invention, the preparation method uses templates with different structures in combination with specific processes to obtain a composite membrane with a specific structure; wherein, the number, height, diameter, and spacing of the protrusions on the surface of the composite membrane can be achieved by using templates with different numbers, heights, diameters, and spacings of protrusions.
[0052] In this invention, the polydimethylsiloxane (PDMS) template is prepared by a casting molding method. Specifically, the PDMS reagent is poured into a master mold with a corresponding structure, sculpted using photolithography. After complete curing, the mold is demolded to obtain a soft PDMS mold. The PDMS reagent is Sylgard 184 silicone rubber manufactured by Dow Corning, which is a mixture of vinyl-terminated polydimethylsiloxane, a curing agent (containing hydrogen-containing silicone oil crosslinking agent and platinum catalyst), and a defoamer at a mass ratio of 89:10:1. The prepolymer is then placed in a vacuum (≤-0.09 MPa) for 5-15 minutes to remove micro-bubbles. Finally, it is poured into the master mold and allowed to stand at room temperature for 3-6 hours, followed by heat curing in a 60-75°C oven for 1-2 hours. After curing, it is allowed to cool naturally to room temperature before demolding, thus obtaining the polydimethylsiloxane template with the corresponding structure described in this invention.
[0053] In this invention, the first coating slurry, by mass percentage, comprises 5-16% of a first polymer (e.g., 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or any combination thereof), 20-34% of inorganic materials (e.g., 22%, 24%, 26%, 28%, 30%, 32%, 34%, or any combination thereof), 0.5-2% of a second polymer (e.g., 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, or any combination thereof), and 60-70% of organic solvents (e.g., 62%, 64%, 66%, 68%, or any combination thereof).
[0054] The second coating slurry comprises, by weight percentage, 10-21% of a first polymer (e.g., a range of 12%, 14%, 16%, 18%, 20%, or any two thereof), 27-45% of inorganic materials (e.g., a range of 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, or any two thereof), 0.5-2% of a second polymer (e.g., a range of 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, or any two thereof), and 40-60% of organic solvents (e.g., a range of 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, or any two thereof).
[0055] Preferably, at 25°C, the viscosity of the first coating slurry is 3000~10000 cp, for example, it can be 3500 cp, 4000 cp, 4500 cp, 5000 cp, 5500 cp, 6000 cp, 6500 cp, 7000 cp, 7500 cp, 8000 cp, 8500 cp, 9000 cp, 9500 cp, or any combination thereof; the viscosity of the second coating slurry is 10000~50000 cp, for example, it can be 12000 cp, 14000 cp, 16000 cp, 18000 cp, 20000 cp, 22000 cp, 24000 cp, 26000 cp, 28000 cp, 30000 cp, 32000 cp, 34000 cp. A range consisting of cp, 36000 cp, 38000 cp, 40000 cp, 42000 cp, 44000 cp, 46000 cp, 48000 cp, or any two of these.
[0056] In this invention, by controlling the first coating slurry to have a lower solid content and lower viscosity, it is more conducive to penetration and obtaining a first surface with a specific roughness; by controlling the second coating slurry to have a higher solid content and higher viscosity, it covers the second template and is more conducive to obtaining a second surface with a specific roughness.
[0057] The present invention does not particularly limit the type of the second polymer, as long as it meets the conventional application in the art. For example, the second polymer includes a hydrophilic polymer, preferably at least one of polyvinylpyrrolidone, polyvinyl alcohol, and polypropylene glycol.
[0058] In this invention, the addition of a second polymer helps to create more uniform pores.
[0059] The present invention does not particularly limit the type of organic solvent, as long as it can dissolve the materials of the first coating layer and the second coating layer. For example, the organic solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, and diethyl sulfoxide.
[0060] In this invention, the preparation methods of the first coating slurry and the second coating slurry are each independent: mixing and stirring the first polymer and inorganic material with an organic solvent, and then adding the second polymer and mixing and stirring to obtain the slurry.
[0061] In some specific embodiments of the present invention, the coating speed in step (2) is 1~10 m / min, for example, it can be a range of 1 m / min, 2 m / min, 3 m / min, 4 m / min, 5 m / min, 6 m / min, 7 m / min, 8 m / min, 9 m / min or any combination thereof.
[0062] In this invention, by controlling the viscosity of the slurry and the coating speed within the above-mentioned range, the penetration rate of the slurry on the grid substrate can be controlled, and the surface roughness Ra of the first surface can be further adjusted to obtain a first surface with a specific roughness.
[0063] Preferably, the pre-evaporation temperature in step (2) is 50~110℃, for example, it can be a range of 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, 105℃ or any two of these; the time is 1~5min, for example, it can be a range of 2min, 3min, 4min or any two of these.
[0064] It is understood that the phase transformation in step (2) includes immersing the pre-evaporated substrate in a non-solvent bath for phase transformation; the non-solvent bath includes a non-solvent.
[0065] The present invention does not specifically limit the type of non-solvent, as long as it can achieve phase transformation. For example, the non-solvent used in the phase transformation in step (2) includes at least one of water, methanol, ethanol, n-propanol, isopropanol, and n-butanol.
[0066] Preferably, the phase transition time in step (2) is 0.5 to 3 hours, for example, it can be a range of 1 hour, 1.5 hours, 2 hours, 2.5 hours or any two of these.
[0067] The present invention does not impose a particular limitation on the phase transition temperature, but in order to improve the consistency of the composite membrane, the phase transition temperature in step (2) can be 30~90℃, specifically 40℃, 50℃, 60℃, 70℃, 80℃ or any combination thereof.
[0068] Preferably, the peeling rate of the first polydimethylsiloxane template in step (2) is 1~10 m / min, for example, it can be a range of 1.5 m / min, 2 m / min, 3 m / min, 4 m / min, 5 m / min, 6 m / min, 7 m / min, 8 m / min, 9 m / min or any combination thereof; the peeling force is 1~5 N / cm. 2 For example, it can be 1.2 N / cm 2 1.5 N / cm 2 1.8 N / cm 2 2 N / cm 2 2.2 N / cm 2 2.5 N / cm 2 2.8 N / cm 2 3 N / cm 2 3.2 N / cm 2 3.5 N / cm 2 3.8 N / cm 2 4 N / cm 2 4.2 N / cm 2 4.5 N / cm 2 4.8 N / cm 2 Or a range of values consisting of any two of them.
[0069] In this invention, controlling the peeling rate and peeling force within the above-mentioned range is beneficial for obtaining a first surface with a specific roughness.
[0070] Preferably, step (3) further includes, before coating, bonding a second polydimethylsiloxane template to the side of the first coating layer away from the substrate.
[0071] Preferably, the coating speed in step (3) is 0.5~2.5 m / min, for example, it can be a range of 0.6 m / min, 0.8 m / min, 1 m / min, 1.2 m / min, 1.4 m / min, 1.6 m / min, 1.8 m / min, 2 m / min, 2.2 m / min, 2.4 m / min or any two of these.
[0072] Preferably, the pre-evaporation and phase transformation process in step (3) is selected from the same range as in step (2).
[0073] Preferably, step (3) further includes stripping the second polydimethylsiloxane template after the phase transformation.
[0074] Preferably, the peeling rate for the second polydimethylsiloxane template is 1~10 m / min, for example, it can be a range of 1.5 m / min, 2 m / min, 3 m / min, 4 m / min, 5 m / min, 6 m / min, 7 m / min, 8 m / min, 9 m / min, or any combination thereof; the peeling force is 1~5 N / cm. 2 For example, it can be 1.2 N / cm 2 1.5 N / cm 2 1.8 N / cm 2 2 N / cm 2 2.2 N / cm 2 2.5 N / cm 2 2.8 N / cm 2 3 N / cm 2 3.2 N / cm 2 3.5 N / cm 2 3.8 N / cm 2 4 N / cm 2 4.2 N / cm 2 4.5 N / cm 2 4.8 N / cm 2 Or a range of values consisting of any two of them.
[0075] In this invention, controlling the peeling rate and peeling force within the above-mentioned range is beneficial for obtaining a second surface with a specific roughness.
[0076] In this invention, the method for preparing the composite membrane is not limited to the method described above; any method capable of preparing the composite membrane with the specific structure of this invention is acceptable.
[0077] The present invention also provides an alkaline water electrolysis device, wherein the alkaline water electrolysis device comprises at least one of the following: (1) The composite diaphragm described in the first aspect; (2) The composite diaphragm prepared by the preparation method described in the second aspect.
[0078] Preferably, the alkaline water electrolysis device includes an electrolysis cell, which includes an anode, the composite membrane described in the first aspect, and a cathode arranged sequentially; the first surface of the composite membrane is attached to the anode, and the second surface is attached to the cathode.
[0079] The numerical range described in this invention includes not only the point values listed above, but also any point values within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values included in the range.
[0080] The technical solutions provided by the present invention will be clearly and completely described below with reference to embodiments and comparative examples. Obviously, the specific embodiments described are only some embodiments of the present invention, and not all embodiments.
[0081] All materials used in this invention are commercially available or prepared using conventional methods; unless otherwise specified, the materials used in this invention are as follows: Substrate: Polyphenylene sulfide mesh substrate, 260μm thick, 50 mesh, purchased from Ryton PPS by Zisaifa Filtration Technology (Suzhou) Co., Ltd.
[0082] Polysulfone: Wharton Technology Co., Ltd. VG2000.
[0083] Polyetheretherketone (PEEK): Purchased from Solvay (KetaSpire® KT-881).
[0084] Polyethersulfone: BASF Ultrason® E2010.
[0085] Polyvinylpyrrolidone (PVP): K90 from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0086] Example 1 This embodiment provides a composite membrane, which includes a first coating layer, a substrate, and a second coating layer disposed sequentially.
[0087] The side of the first coating layer away from the substrate is the first surface, which has a roughness Ra of 3 μm and is covered with arc-shaped dot-like protrusions; wherein the number of arc-shaped dot-like protrusions is 150 per mm. 2 The distance between any two adjacent arc-shaped protrusions is 80 μm, the diameter of the arc-shaped protrusions is 40 μm, the average height is 30 μm, and the RSD of the height is 2%.
[0088] The side of the second coating layer away from the substrate is the second surface, which has a roughness Ra of 0.4 μm and is covered with arc-shaped dot-like protrusions; wherein the number of arc-shaped dot-like protrusions is 25 per mm. 2 The distance between any two adjacent arc-shaped dot protrusions is 250 μm, the diameter of the arc-shaped dot protrusions is 5 μm, and the average height is 2.5 μm.
[0089] The difference in roughness Ra between the first surface and the second surface is 2.6 μm.
[0090] The first coating layer comprises polysulfone and zirconium dioxide in a mass ratio of 1:2.7; the second coating layer comprises polysulfone and zirconium dioxide in a mass ratio of 1:3.
[0091] The thickness of the first coating layer at the flat area (i.e., the thickness excluding the protrusions) is the same as the thickness of the second coating layer at the flat area; the thickness of the composite membrane is 420 μm.
[0092] This embodiment provides a method for preparing the composite separator, specifically including the following steps: (1) By mass percentage, 10% polysulfone, 27% zirconium dioxide, 1% polyvinylpyrrolidone and 62% N-methylpyrrolidone are mixed evenly to obtain a first coating slurry with a viscosity of 5000cp (25°C); in addition, by mass percentage, 13% polysulfone, 39% zirconium dioxide, 1% polyvinylpyrrolidone and 47% N-methylpyrrolidone are mixed evenly to obtain a second coating slurry with a viscosity of 20000cp (25°C).
[0093] (2) Fix the customized first polydimethylsiloxane template with the corresponding structure, and lay the substrate flat on one side of the first polydimethylsiloxane template. Control the width of the slit to the corresponding membrane thickness. Then, apply the first coating slurry to a surface of the substrate away from the first polydimethylsiloxane template at a speed of 2 m / min. After pre-evaporation at 80°C for 3 min, immerse it in a non-solvent bath containing 70°C water for phase inversion for 2 h. Peel at a rate of 5 m / min and a peeling force of 2.5 N / cm. 2 The first polydimethylsiloxane template is peeled off under certain conditions to obtain a substrate with a first coating layer on its surface; (3) A customized second polydimethylsiloxane template with a corresponding structure is composited onto the side of the first coating layer away from the substrate, and the second coating slurry is coated onto the surface of the substrate away from the first coating layer at a speed of 1 m / min. After pre-evaporation at 80°C for 3 min, it is immersed in a non-solvent bath containing water at 70°C for 2 h for phase inversion, and the peeling rate is 5 m / min with a peeling force of 2.5 N / cm. 2The second polydimethylsiloxane template was peeled off under certain conditions to obtain the composite membrane.
[0094] Example 2 This embodiment provides a composite membrane, which includes a first coating layer, a substrate, and a second coating layer disposed sequentially.
[0095] The side of the first coating layer furthest from the substrate is the first surface, which has a roughness Ra of 2 μm and is covered with arc-shaped dot-like protrusions; wherein the number of arc-shaped dot-like protrusions is 100 per mm. 2 The distance between any two adjacent arc-shaped dot protrusions is 100 μm, the diameter of the arc-shaped dot protrusions is 50 μm, the average height is 10 μm, and the RSD of the height is 3.5%.
[0096] The side of the second coating layer away from the substrate is the second surface, which has a roughness Ra of 0.35 μm and is covered with arc-shaped dot-like protrusions; the number of these protrusions is 10 per mm. 2 The distance between any two adjacent arc-shaped dot protrusions is 300 μm, the diameter of the arc-shaped dot protrusions is 8 μm, and the average height is 1 μm.
[0097] The difference in roughness Ra between the first surface and the second surface is 1.65 μm.
[0098] The first coating layer is made of polyetheretherketone and barium sulfate in a mass ratio of 1:4; the second coating layer is made of polyetheretherketone and barium sulfate in a mass ratio of 1:4.4.
[0099] The thickness of the first coating layer at the flat area is the same as the thickness of the second coating layer at the flat area; the thickness of the composite membrane is 500 μm.
[0100] This embodiment provides a method for preparing the composite separator, specifically including the following steps: (1) By mass percentage, 6% polyetheretherketone, 24% barium sulfate, 2% polyvinylpyrrolidone and 68% N-methylpyrrolidone are mixed evenly to obtain a first coating slurry with a viscosity of 3000cp (25°C); In addition, by mass percentage, 11% polyetheretherketone, 44% barium sulfate, 1% polyvinylpyrrolidone and 44% N-methylpyrrolidone are mixed evenly to obtain a second coating slurry with a viscosity of 30000cp (25°C); (2) Fix the customized first polydimethylsiloxane template with the corresponding structure, and lay the substrate flat on one side of the first polydimethylsiloxane template. Control the width of the slit to the corresponding membrane thickness. Then, apply the first coating slurry to a surface of the substrate away from the first polydimethylsiloxane template at a speed of 2 m / min. After pre-evaporation at 50°C for 5 min, immerse it in a non-solvent bath containing water at 40°C for phase inversion for 3 h. Peel at a peeling rate of 10 m / min and a peeling force of 5 N / cm. 2 The first polydimethylsiloxane template is peeled off under certain conditions to obtain a substrate with a first coating layer on its surface; (3) A customized second polydimethylsiloxane template with a corresponding structure is composited onto the side of the first coating layer away from the substrate, and the second coating slurry is coated onto the surface of the substrate away from the first coating layer at a speed of 1 m / min. Then, after pre-evaporation at 110°C for 1 min, it is immersed in a non-solvent bath containing water at 80°C for phase inversion for 3 h, with a peeling rate of 6 m / min and a peeling force of 3 N / cm. 2 The second polydimethylsiloxane template was peeled off under certain conditions to obtain the composite membrane.
[0101] Example 3 This embodiment provides a composite membrane, which includes a first coating layer, a substrate, and a second coating layer disposed sequentially.
[0102] The side of the first coating layer furthest from the substrate is the first surface, which has a roughness Ra of 3.5 μm and is covered with arc-shaped dot-like protrusions; wherein the number of arc-shaped dot-like protrusions is 200 per mm. 2 The distance between any two adjacent arc-shaped protrusions is 90 μm, the diameter of the arc-shaped protrusions is 45 μm, the average height is 50 μm, and the RSD of the height is 1.8%.
[0103] The side of the second coating layer furthest from the substrate is the second surface, which has a roughness Ra of 0.5 μm and is covered with arc-shaped dot-like protrusions; the number of these protrusions is 50 per mm. 2 The distance between any two adjacent arc-shaped dot protrusions is 280μm, the diameter of the arc-shaped dot protrusions is 2μm, and the average height is 5μm.
[0104] The difference in roughness Ra between the first surface and the second surface is 3 μm.
[0105] The first coating layer is made of polyethersulfone and zirconium oxide in a mass ratio of 1:2; the second coating layer is made of polyethersulfone and zirconium oxide in a mass ratio of 1:3.
[0106] The thickness of the first coating layer at the flat area is the same as the thickness of the second coating layer at the flat area; the thickness of the composite diaphragm is 390 μm.
[0107] This embodiment provides a method for preparing the composite separator, specifically including the following steps: (1) By mass percentage, 10% polyethersulfone, 20% zirconium oxide, 0.5% polyvinylpyrrolidone and 69.5% N-methylpyrrolidone are mixed evenly to obtain a first coating slurry with a viscosity of 5000cp (25°C); in addition, by mass percentage, 13% polyethersulfone, 39% zirconium oxide, 1% polyvinylpyrrolidone and 47% N-methylpyrrolidone are mixed evenly to obtain a second coating slurry with a viscosity of 20000cp (25°C).
[0108] (2) Fix the customized first polydimethylsiloxane template with the corresponding structure, and lay the substrate flat on one side of the first polydimethylsiloxane template. Control the width of the slit to the corresponding membrane thickness. Then, apply the first coating slurry to a surface of the substrate away from the first polydimethylsiloxane template at a speed of 2 m / min. After pre-evaporation at 110°C for 1 min, immerse it in a non-solvent bath containing water at 80°C for phase inversion for 1 h. Peel at a rate of 3 m / min and a peeling force of 2 N / cm. 2 The first polydimethylsiloxane template is peeled off under certain conditions to obtain a substrate with a first coating layer on its surface; (3) A customized second polydimethylsiloxane template with a corresponding structure is composited onto the side of the first coating layer away from the substrate, and the second coating slurry is coated onto the surface of the substrate away from the first coating layer at a speed of 1 m / min. After pre-evaporation at 50°C for 5 min, it is immersed in a non-solvent bath containing water for phase inversion for 1 h, with a peeling rate of 10 m / min and a peeling force of 5 N / cm. 2 The second polydimethylsiloxane template was peeled off under certain conditions to obtain the composite membrane.
[0109] Example 4 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the dot-like protrusion structure on the first and second surfaces is a coral-like protrusion structure. The roughness Ra of the first surface is 5.4 μm, and the RSD of the protrusion height is 2.3%. The roughness Ra of the second surface is 0.45 μm. The preparation method uses a polydimethylsiloxane template with a corresponding structure. Other materials, structural parameters, and preparation methods are the same as in Embodiment 1.
[0110] Example 5 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the Ra of the first surface is 3.5 μm and the number of dot-like protrusions is 300 per mm. 2 The spacing between any two adjacent dot-shaped protrusions is 60 μm, the diameter of the dot-shaped protrusions is 20 μm, the average height of the protrusions is 30 μm, and the RSD of the height is 2.4%. The preparation method uses a polydimethylsiloxane template with the corresponding structure. Other materials, structural parameters, and preparation methods are the same as in Example 1.
[0111] Example 6 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the Ra of the first surface is 2.6 μm and the number of dot-like protrusions is 40 per mm. 2 The spacing between any two adjacent dot-shaped protrusions is 100 μm, the diameter of the dot-shaped protrusion is 50 μm, the average height of the protrusion is 30 μm, and the RSD of the height is 3.4%. The preparation method uses a polydimethylsiloxane template with the corresponding structure, and other materials, structural parameters and preparation methods are the same as in Example 1.
[0112] Example 7 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the Ra of the first surface is 2.4 μm, and the number of arc-shaped dot-like protrusions is 150 per mm. 2 The spacing between any two adjacent dot-shaped protrusions is 55 μm, the diameter of the dot-shaped protrusions is 52 μm, the average height is 30 μm, and the RSD of the height is 1.8%. The preparation method uses a polydimethylsiloxane template with the corresponding structure, and other materials, structural parameters, and preparation methods are the same as in Example 1.
[0113] Example 8 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the Ra of the first surface is 3.8 μm, and the number of arc-shaped dot-like protrusions is 150 per mm. 2 The spacing between any two adjacent dot-shaped protrusions is 150 μm, the diameter of the dot-shaped protrusions is 15 μm, the average height is 30 μm, and the RSD of the height is 3.2%. The preparation method uses a polydimethylsiloxane template with the corresponding structure, and other materials, structural parameters, and preparation methods are the same as in Example 1.
[0114] Example 9 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the average height of the dot-shaped protrusions on the first surface is 5 μm, the Ra of the first surface is 2.4 μm, and the number of arc-shaped dot-shaped protrusions is 150 per mm. 2The spacing between any two adjacent dot-shaped protrusions is 80 μm, the diameter of the dot-shaped protrusion is 40 μm, and the RSD of the height is 2.9%. The preparation method uses a polydimethylsiloxane template with the corresponding structure, and other materials, structural parameters and preparation methods are the same as in Example 1.
[0115] Example 10 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the average height of the dot-shaped protrusions on the first surface is 55 μm, the Ra of the first surface is 4 μm, and the number of arc-shaped dot-shaped protrusions is 150 per mm. 2 The spacing between any two adjacent dot-shaped protrusions is 80 μm, the diameter of the dot-shaped protrusion is 40 μm, and the RSD of the height is 3.5%. The preparation method uses a polydimethylsiloxane template with the corresponding structure, and other materials, structural parameters and preparation methods are the same as in Example 1.
[0116] Example 11 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the RSD of the height of the dot-shaped protrusions on the first surface is 6%, the Ra of the first surface is 2.8 μm, and the number of arc-shaped dot-shaped protrusions is 150 per mm. 2 The spacing between any two adjacent dot-shaped protrusions is 80 μm, the diameter of the dot-shaped protrusion is 40 μm, and the average height of the protrusion is 30 μm. The preparation method uses a polydimethylsiloxane template with the corresponding structure, and other materials, structural parameters, and preparation methods are the same as in Example 1.
[0117] Example 12 This embodiment provides a composite diaphragm, which differs from Embodiment 1 in that the roughness Ra of the second surface is 0.51 μm, and the second surface is distributed with arc-shaped dot-like protrusions; wherein the number of arc-shaped dot-like protrusions is 60 per mm. 2 The spacing between any two adjacent arc-shaped dot protrusions is 150 μm, the diameter of the arc-shaped dot protrusions is 1 μm, and the average height is 2.5 μm; the preparation method uses a polydimethylsiloxane template with the corresponding structure; the RSD of the height of the first surface is 1.8%; other materials, structural parameters and preparation methods are the same as in Example 1.
[0118] Example 13 This embodiment provides a composite diaphragm, which differs from Embodiment 1 in that the roughness Ra of the second surface is 0.41 μm, and the second surface is distributed with arc-shaped dot-like protrusions; wherein the number of arc-shaped dot-like protrusions is 5 per mm. 2The spacing between any two adjacent arc-shaped dot protrusions is 300 μm, the diameter of the arc-shaped dot protrusions is 10 μm, and the average height is 2.5 μm; the preparation method uses a polydimethylsiloxane template with the corresponding structure; the RSD of the height of the first surface is 1.9%; other materials, structural parameters and preparation methods are the same as in Example 1.
[0119] Example 14 This embodiment provides a composite diaphragm, which differs from Embodiment 1 in that the roughness Ra of the second surface is 0.38 μm, and the second surface is distributed with arc-shaped dot-like protrusions; wherein the number of arc-shaped dot-like protrusions is 25 per mm. 2 The spacing between any two adjacent arc-shaped dot-shaped protrusions is 50 μm, the diameter of the arc-shaped dot-shaped protrusions is 15 μm, and the average height is 2.5 μm; the preparation method uses a polydimethylsiloxane template with the corresponding structure; the RSD of the height of the first surface is 2.5%; other materials, structural parameters, and preparation methods are the same as in Example 1.
[0120] Example 15 This embodiment provides a composite diaphragm, which differs from Embodiment 1 in that the roughness Ra of the second surface is 0.45 μm, and the second surface is distributed with arc-shaped dot-like protrusions; wherein the number of arc-shaped dot-like protrusions is 25 per mm. 2 The spacing between any two adjacent arc-shaped dot protrusions is 550 μm, the diameter of the arc-shaped dot protrusions is 0.5 μm, and the average height is 2.5 μm; the preparation method uses a polydimethylsiloxane template with the corresponding structure; the RSD of the height of the first surface is 2.4%; other materials, structural parameters, and preparation methods are the same as in Example 1.
[0121] Example 16 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the height of the dot-shaped protrusions on the second surface is 0.5 μm, the surface roughness Ra is 0.36 μm, and the number of arc-shaped dot-shaped protrusions is 25 per mm. 2 The spacing between any two adjacent arc-shaped dot protrusions is 250 μm, and the diameter of the arc-shaped dot protrusions is 5 μm; the preparation method uses a polydimethylsiloxane template with the corresponding structure; the RSD of the height of the first surface is 2.6%; other materials, structural parameters and preparation methods are the same as in Example 1.
[0122] Example 17 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the height of the dot-shaped protrusions on the second surface is 7 μm, the roughness Ra of the second surface is 0.44 μm, and the number of arc-shaped dot-shaped protrusions is 25 per mm. 2 The spacing between any two adjacent arc-shaped dot protrusions is 250 μm, and the diameter of the arc-shaped dot protrusions is 5 μm; the preparation method uses a polydimethylsiloxane template with the corresponding structure; the RSD of the height of the first surface is 2.4%; other materials, structural parameters and preparation methods are the same as in Example 1.
[0123] Example 18 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the second surface does not form a raised structure with the aid of a template. In the preparation method, the coating slurry is directly coated onto the surface of the substrate away from the first coating layer, and then subsequent pre-evaporation and phase inversion processes are performed. Other materials, structural parameters and preparation methods are the same as in Embodiment 1.
[0124] Comparative Example 1 This comparative example provides a composite diaphragm, which differs from Example 1 in that the roughness Ra of the first surface is 9 μm, and the first surface is distributed with arc-shaped dot-like protrusions; wherein the number of arc-shaped dot-like protrusions is 150 per mm. 2 The spacing between any two adjacent arc-shaped dot-shaped protrusions is 80 μm, the diameter of the arc-shaped dot-shaped protrusions is 40 μm, the average height is 30 μm, and the RSD of the height is 2.3%. In the preparation method, the coating speed in step (2) is adjusted to 20 m / min, and the peeling force is 10 N / cm. 2 The peeling rate was 15 m / min, and the other materials, structural parameters and preparation methods were the same as in Example 1.
[0125] Comparative Example 2 This comparative example provides a composite diaphragm, which differs from Example 1 in that the roughness Ra of the first surface is 0.6 μm, and the first surface is distributed with arc-shaped dot-like protrusions; wherein the number of arc-shaped dot-like protrusions is 150 per mm. 2 The spacing between any two adjacent arc-shaped dot-shaped protrusions is 80 μm, the diameter of the arc-shaped dot-shaped protrusions is 40 μm, the average height is 30 μm, and the RSD of the height is 1.9%. In the preparation method, the coating speed in step (2) is adjusted to 0.5 m / min, and the peeling force is 1 N / cm. 2 The peeling rate was 0.5 m / min, and the other materials, structural parameters and preparation methods were the same as in Example 1.
[0126] Comparative Example 3 This comparative example provides a composite diaphragm, which differs from Example 1 in that the roughness of the first surface is 3.1 μm and the height RSD is 2.1%; the roughness Ra of the second surface is 1 μm, and the second surface is distributed with arc-shaped dot-like protrusions; wherein the number of arc-shaped dot-like protrusions is 25 per mm. 2 The spacing between any two adjacent arc-shaped dot-shaped protrusions is 250 μm, the diameter of the arc-shaped dot-shaped protrusions is 5 μm, and the average height is 2.5 μm. In the preparation method, the coating speed in step (3) is adjusted to 3 m / min, and the peeling force is 6 N / cm. 2 The peeling rate was 10 m / min, and the other materials, structural parameters and preparation methods were the same as in Example 1.
[0127] Comparative Example 4 This comparative example provides a composite membrane, which differs from Example 1 in that the first and second surfaces do not contain protruding structures. In the preparation method, steps (2) and (3) do not use a template; the slurry is directly coated onto the substrate surface, and then subsequent pre-evaporation and phase transformation steps are performed. The specific materials and processes are the same as in Example 1.
[0128] Performance testing (1) Sheet resistance: Four diaphragm samples with a diameter of 4 cm were cut from a flat area of the composite diaphragm. The samples were immersed in 30% KOH solution for 24 hours. After that, they were taken out and placed in a sheet resistance testing fixture (test diameter 2 cm). The four-probe method of an electrochemical workstation was used to test the resistance at 25°C. The four diaphragms were placed in the fixture one after another to obtain the resistance values of the four diaphragms. Then, the average resistance value of the four diaphragms was taken, and the average resistance value was multiplied by the test area of the diaphragm (3.14 cm²). 2 ), that is, the surface resistance (Ω•cm) is obtained. 2 ).
[0129] (2) Electrolytic cell voltage: The electrolysis was carried out under normal pressure and constant temperature of 80℃, using 30 wt% KOH aqueous solution as electrolyte, Raney nickel as cathode catalyst and porous nickel as anode catalyst, and the anode and cathode were isolated by a composite diaphragm; the electrolysis chamber was controlled at 5000 A / m 2 The constant current density is constant current operation. After the operating conditions stabilize and the voltage fluctuation is stable, the steady-state working voltage of the electrolysis chamber is collected and recorded. The test is repeated three times and the average value is taken to obtain the standard working voltage under this condition.
[0130] (3) Stability: The stability of the composite diaphragm is characterized by the change (reduction rate) of the bubble point before and after 500h of circulation; specifically: reduction rate = 100% × (bubble point before tanking - bubble point after tanking) / bubble point before tanking; the bubble point test method is to inject water into one side of the composite diaphragm and pressurize the other side with compressed air at a speed of 2 bar / min to observe the generation of bubbles. The pressure of the first bubble is the bubble point value of the composite diaphragm.
[0131] The specific test results are shown in Table 1.
[0132] Table 1 As shown in Table 1, the composite diaphragm provided by this invention employs a specific structural design, namely, two surfaces with different roughnesses. The first surface has dotted protrusions. In application, the first surface is close to the anode, and the second surface is close to the cathode, which increases the effective working area of the composite diaphragm. This results in a short residence time of bubbles on its surface, solving the problem of voltage rise caused by bubble shielding effect in alkaline water electrolysis hydrogen production cells under high current density in existing technologies. Simultaneously, it exhibits low sheet resistance, high bubble point, and high stability. The sheet resistance of the composite diaphragm is 0.162~0.170 Ω·cm. 2 The electrolytic cell voltage was 1.70~1.81mV, the bubble point was 3.3~3.9bar, and the bubble point reduction rate after 500h of cycling was 13.51~30.56%.
[0133] As can be seen from Example 1 and Comparative Examples 1-3, when the roughness of the first and second surfaces is not within a specific range, the surface resistance of the resulting composite diaphragm increases, the voltage of the electrolytic cell increases, or the stability deteriorates.
[0134] As can be seen from the comparison between Example 1 and Comparative Example 4, compared with conventional composite membranes (which have no protruding structure and are prepared by conventional coating process), the composite membrane provided by the present invention has a lower electrolytic cell voltage and better stability.
[0135] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A composite diaphragm, characterized in that, The composite diaphragm has a first surface and a second surface disposed opposite to each other; The roughness Ra of the first surface is 0.8~6μm; The roughness Ra of the second surface is ≤0.7μm; The first surface has dotted protrusions.
2. The composite diaphragm according to claim 1, characterized in that, The difference in roughness Ra between the first surface and the second surface is 1.5~5μm.
3. The composite diaphragm according to claim 1 or 2, characterized in that, The dot-shaped protrusion structure is selected from the dot-shaped protrusion structure without sharp edges, preferably at least one of the arc protrusion structure, mushroom protrusion structure, and coral protrusion structure, and more preferably the arc protrusion structure; Preferably, the first surface satisfies at least one of the following: (a) The number of dot-like protrusions on the first surface is 50 to 250 per mm. 2 ; (b) The distance between any two adjacent point-like protrusions on the first surface is 60~100μm; (c) The diameter of the dot-like protrusions on the first surface is 20~50μm; (d) The height of the dot-like protrusions on the first surface is 10~50μm; (e) The relative standard deviation (RSD) of the height of the dotted protrusions on the first surface is 0 to 4%.
4. The composite diaphragm according to any one of claims 1 to 3, characterized in that, The second surface is distributed with dotted protrusions; Preferably, the second surface satisfies at least one of the following: (a) The number of dot-like protrusions on the second surface is 10 to 50 per mm. 2 ; (b) The distance between any two adjacent point-like protrusions on the second surface is 100~300μm; (c) The diameter of the dot-like protrusions on the second surface is 1~10 μm; (d) The height of the dot-shaped protrusions on the second surface is 1~5μm.
5. The composite diaphragm according to any one of claims 1 to 4, characterized in that, The composite membrane includes a first coating layer, a substrate, and a second coating layer disposed sequentially. The side of the first coating layer away from the substrate is the first surface; the side of the second coating layer away from the substrate is the second surface. The first coating layer and the second coating layer may be made of the same or different materials, and each independently comprises a first polymer and an inorganic material; Preferably, the mass ratio of the first polymer to the inorganic material in the first coating layer is 1:(1.3~8), and the mass ratio of the first polymer to the inorganic material in the second coating layer is 1:(1.2~5); Preferably, the first polymer comprises at least one of polysulfone, polyethersulfone, polyphenylene sulfone, and polyetheretherketone; Preferably, the inorganic material includes at least one of zirconium dioxide, titanium dioxide, barium sulfate, and barium zirconate.
6. The composite diaphragm according to claim 5, characterized in that, The thickness of the substrate is 240~300μm; Preferably, the thickness of the composite diaphragm is 390~520μm.
7. A method for preparing a composite separator according to any one of claims 1 to 6, characterized in that, The preparation method includes the following steps: (1) Provide a substrate; and lay the substrate flat and fix it to one side of the first polydimethylsiloxane template; (2) Prepare a first coating slurry and coat the first coating slurry onto a surface of the substrate away from the first polydimethylsiloxane template. Then, the substrate is subjected to pre-evaporation, phase inversion and peeling off of the first polydimethylsiloxane template in sequence to obtain a substrate with the first coating layer on the surface. (3) Prepare a second coating slurry and coat the second coating slurry onto the surface of the substrate away from the first coating layer, and then perform pre-evaporation and phase inversion in sequence to obtain the composite membrane.
8. The preparation method according to claim 7, characterized in that, The first coating slurry comprises, by mass percentage, 5-16% of a first polymer, 20-34% of inorganic materials, 0.5-2% of a second polymer, and 60-70% of organic solvents; The second coating slurry comprises, by mass percentage, 10-21% of a first polymer, 27-45% of inorganic materials, 0.5-2% of a second polymer, and 40-60% of organic solvents; Preferably, at 25°C, the viscosity of the first coating slurry is 3000~10000cp, and the viscosity of the second coating slurry is 10000~50000cp.
9. The preparation method according to claim 7 or 8, characterized in that, The coating speed in step (2) is 1~10 m / min; Preferably, the pre-evaporation temperature in step (2) is 50~110℃ and the time is 1~5min; Preferably, the phase transformation time in step (2) is 0.5~3h; Preferably, the peeling rate of the first polydimethylsiloxane template in step (2) is 1~10 m / min, and the peeling force is 1~5 N / cm. 2 ; Preferably, step (3) further includes, before coating, bonding a second polydimethylsiloxane template to the side of the first coating layer away from the substrate; Preferably, the coating speed in step (3) is 0.5~2.5 m / min; Preferably, the pre-evaporation and phase transformation process in step (3) is selected from the same range as in step (2); Preferably, step (3) further includes stripping the second polydimethylsiloxane template after the phase transformation; Preferably, the peeling rate of the second polydimethylsiloxane template is 1~10 m / min, and the peeling force is 1~5 N / cm. 2 .
10. An alkaline water electrolysis device, characterized in that, The alkaline water electrolysis device includes at least one of the following: (1) The composite diaphragm according to any one of claims 1 to 6; (2) The composite diaphragm prepared by the preparation method according to any one of claims 7 to 9; Preferably, the alkaline water electrolysis device includes an electrolysis cell, which includes an anode, a composite membrane as described in any one of claims 1 to 6, and a cathode arranged sequentially; the first surface of the composite membrane is attached to the anode, and the second surface is attached to the cathode.